Impact of the COVID‐19 pandemic on rural and urban cancer patients' experiences, health behaviors, and perceptions. Issue 4 (3rd March 2022) - Peoples, Anita R.; Oswald, Laura B.; Ose, Jennifer; Daniels, Bailee; Himbert, Caroline; Hathaway, Cassandra A.; Gigic, Biljana; Kirchhoff, Anne C.; Lin, Tengda; Grossman, Douglas; Tward, Jonathan; Varghese, Thomas K.; et al.
Abstract: Purpose: The COVID‐19 pandemic has disrupted many facets of life. We evaluated pandemic‐related health care experiences, COVID‐19 prevention behaviors and measures, health behaviors, and psychosocial outcomes among rural and urban cancer patients. Methods: Among 1, 472 adult cancer patients, who visited Huntsman Cancer Institute in the past 4 years and completed a COVID‐19 survey (August‐September 2020), we assessed the impact of the pandemic on medical appointments, prevention/health behaviors, and psychosocial factors, stratified by urbanicity. Findings: Mean age was 61 years, with 52% female, 97% non‐Hispanic White, and 27% were residing in rural areas. Rural versus urban patients were more likely to be older, not employed, uninsured, former/current smokers, consume alcohol, and have pandemic‐related changes/cancellations in surgery appointments (all P <.05). Changes/cancellations in other health care access (eg, doctor's visits) were also common, particularly among urban patients. Urban versus rural patients were more likely to socially distance, use masks and hand sanitizer, and experience changes in exercise habits and in their daily lives (all P <.05). Less social interaction and financial stress were common among cancer patients but did not differ by urbanicity. Conclusions: These findings suggest that the COVID‐19 pandemic had a substantial impact on cancer patients, with several challenges specific to rural patients. This comprehensive study provides unique insights into the first 6 months of COVID‐19 pandemic‐related experiences and continuity of care among rural and urban cancer patients predominantly from Utah. Further research is needed to better characterize the pandemic's short‐ and long‐term effects on rural and urban cancer patients and appropriate interventions.